The bachelor [large type] - Jeffries, Sabrina (Jeffries, Sabrina. Duke dynasty, 2023)
"Lady Gwyn Drake has long protected her family's reputation by hiding an imprudent affair from her youth. But when her former suitor appears at Armitage Hall, manhandling the heiress and threatening to go public with her secrets, it's Gwyn who needs protecting. Her twin brother, Thorn, hires Joshua Wolfe, the estate's gamekeeper, to keep her safe in London during her debut. As a war hero, Joshua feels obligated to fulfill the assignment he has accepted. But as a man, it's torment to be so very close to the beauty he's fought to ignore . . . With handsome Joshua monitoring her every move, Gwyn would prefer to forget both the past and the parade of money-seeking bachelors at her coming out. But Joshua is unmoved by her attempts at flirtation, and the threat of blackmail still hangs over her. With danger closing in, Gwyn must decide which is the greater risk: deflecting a scoundrel's attempts to sabotage her - or revealing her whole heart to the rugged bodyguard she can't resist."--